Peran Kepemimpinan Kepala Sekolah dalam Mengembangkan Kualitas - Nuruddin, Nuruddin; Subando, Joko (TSAQOFAH, 2026)
This study aimed to analyze the role of principal leadership in improving the quality of teaching and learning in schools, given the principal’s strategic position in directing, guiding, and motivating teachers and education staff so that the instructional process is effective, innovative, and quality-oriented. A qualitative approach with a case study method was employed, using interviews, observations, and documentation to explore the principal’s leadership practices in the context of instructional management. The findings show that principal leadership plays a crucial role in enhancing learning quality through the design of well-directed academic programs, continuous professional development for teachers, the creation of a school climate that is conducive to teaching and learning, and the strengthening of systematic academic supervision. In addition, a participatory and visionary leadership style was found to encourage the engagement of all school stakeholders in efforts to improve the quality of instruction. These results affirm that principal leadership is a key factor in realizing high-quality and competitive learning at the school level.